2021
DOI: 10.3389/fimmu.2021.777927
|View full text |Cite
|
Sign up to set email alerts
|

Immune Profiling of Cord Blood From Preterm and Term Infants Reveals Distinct Differences in Pro-Inflammatory Responses

Abstract: BackgroundPreterm infants are highly vulnerable to infectious disease. While many factors are likely to contribute to this enhanced susceptibility, the immature nature of the preterm immune system is postulated as one key factor.MethodsIn our study, we used high-dimensional flow cytometry and cytokine assays to characterise the immune profiles in 25 preterm (range: 30.4-34.1 weeks gestational age) and 25 term infant (range: 37-40 weeks gestational age) cord blood samples.ResultsWe found that preterm infants ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
24
1
Order By: Relevance
“…Our analyses of immune cell profiles showed that decreased odds of being a preterm infant were associated with increased CD4T cells when NDMI 450 was accounted for, and with increased NK and B cell proportions when NDMI 450 was not accounted for. This conflicts with published literature reports that preterm infants exhibited reduced frequencies of CD56 bright NK cells and increased frequencies of CD4+ T cells and transitional B cells [ 19 ]. Additionally, our analyses of glucose tolerance showed an increase in CD8T proportions was associated with a significant decrease in odds of GDM.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our analyses of immune cell profiles showed that decreased odds of being a preterm infant were associated with increased CD4T cells when NDMI 450 was accounted for, and with increased NK and B cell proportions when NDMI 450 was not accounted for. This conflicts with published literature reports that preterm infants exhibited reduced frequencies of CD56 bright NK cells and increased frequencies of CD4+ T cells and transitional B cells [ 19 ]. Additionally, our analyses of glucose tolerance showed an increase in CD8T proportions was associated with a significant decrease in odds of GDM.…”
Section: Discussioncontrasting
confidence: 95%
“…Immune cells in term and preterm labor participate in various phases of the pregnancy. Compared to term infants, preterm infants were observed to have lower proportions of CD56 bright NK cells, CD8+ T cells, and γδ T cells, and increased levels of CD4+ T cells and transitional B cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported dampened responses by human UCB monocytes of babies born to mothers with obesity (15,28,39,40) as well as by splenocytes from pups born to obese dams to LPS stimulation (41). Additional studies indicated increased airway reactivity and aberrant responses to RSV in pups born to dams fed a HFD during gestation (22).…”
Section: Discussionmentioning
confidence: 98%
“…Further studies have revealed differences between the blood of preterm and term infants: Anderson et al reported reduced frequencies of monocytes and CD56 bright NK cells, as well as CD8+ T-cells, and γδ T-cells in preterm infants [ 35 ]. Moreover, controversial data exist regarding the amount of proinflammatory interleukin-6 (IL-6) in cord blood: While Anderson et al reported elevated levels in preterm infants, Sullivan et al detected lower levels in comparison to term infants [ 36 ].…”
Section: Discussionmentioning
confidence: 99%